The Dynamics of Kalijompo Plantation Workers from 1998-2020 - Nurul Fitriyah; M. Al Qautsar Pratama (Criksetra: Jurnal Pendidikan Sejarah, 2026)
Since the period of Dutch Colonial rule, labor work was predominantly carried out by indigenous people, especially those who lacked capital. In plantation areas, laborers became a crucial component of the plantation’s operational structure. Their roles made their presence indispensable to plantation companies. This study examines the socio-economic history of laborers at the Kalijompo Plantation (1998–2020). The method employed is the historical method, including heuristics, source criticism, interpretation, and historiography. The findings indicate that the dynamics of life among Kalijompo Plantation laborers were influenced by social class divisions within the plantation community, which in turn affected workers’ welfare. The relatively subsistence-level lives of the laborers, marked by a lack of economic surplus, contributed to the emergence of false consciousness, shaped by the hegemony of plantation authorities and prevailing social constructions within the community. Entering the 2000s, these subsistence conditions gave rise to forms of hidden resistance (hidden transcripts), such as land burning, obstruction, and theft within the plantation area. In early 2020, workforce reductions and wage cuts occurred, significantly impacting the laborers’ livelihoods.